Evaluating Inhaler Use Technique among Asthma and COPD Patients at a Primary Health Care Unit: A Pilot Study in Selangor Malaysia - Zulfan Zazuli; Kogilavani Ramasamy; I Ketut Adnyana (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Inhaler is the most preferable device to deliver medication in order to treat asthma and Chronic Obstructive Pulmonary Disease (COPD). Incorrect usage of inhaler influences the clinical effectiveness of the delivered drug. A pilot study was conducted to determine the appropriateness of inhaler handling technique among asthma and COPD patients. As many as 92 subjects whom diagnosed with asthma and COPD, aged between 18 to 64 years old were observed in this cross-sectional study. Consenting subjects on inhaler, who attended medical out patients clinic at a primary health care unit in Selangor, Malaysia were asked to demonstrate on how they use the inhaler while an inhaler administration checklist were used to assess each patients inhaler technique. Data was analysed using descriptive statistical methods. Of total 92 patients, a total of 155 devices were used. Only 4 out of 92 patients correctly handles the device (4.3%). In average, a patient made approximately >4 mistakes during pMDI inhalation and >2 mistakes during DPI inhalation. The most common mistake found among pMDI, Turbuhaler and Accuhaler users were unable to hold the breath for approximately 5 seconds in which comprise of ≥80% patients. In conclusion, majority of asthma and COPD patients use their inhaler inaccurately. Patients prescribed by inhalation medications should have routine assessment of their inhaler technique at every visit and corrected if found to be poor.